Edukacja dwujęzyczna i konstruowanie tożsamości etnicznej (na przykładzie mniejszości tubylczych w obszarach Arktyki) - Gmerek, Tomasz (Wydawnictwo Naukowe UAM, 2014)
The article deals with the issue of the relation between education and the processes of the development of ethnic identity in the Arctic. Particular emphasis was placed on reconstructing educational practices and the language policy that is implemented toward indigenous minorities in the circumpolar countries. An attempt was made at examining the relationship between language policy, schooling, and development of ethnic identity of aboriginal minorities in the Far North.
Bilingual Education and the Construction of Ethnic Identity (Arctic Native Minorities Study)
Keywords: bilingual education; ethnic identity; native minorities; Arctic; Circumpolar Region